The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.5488/cmp.4.1.77
|View full text |Cite
|
Sign up to set email alerts
|

On the Critical Behaviour of Random Anisotropy Magnets

Abstract: The effect of a local anisotropy of random orientation on a ferromagnetic phase transition is studied. To this end, a model of a random anisotropy magnet is analysed by means of a field theoretical renormalization group approach. The one-loop result of Aharony about the absence of a 2nd order phase transition for isotropic distribution of random anisotropy axis at space dimension d < 4 is corroborated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 13 publications
(26 reference statements)
3
45
0
Order By: Relevance
“…The absence of ferromagnetic ordering in isotropic RAM was first observed in the renormalization group study of [4] where no accessible fixed points of the renormalization group transformation were obtained for the model within ε = 4 − d expansion. Recently, this result was corroborated by higher-order calculations refined by a resummation technique [5]. The proof of [6,7] used arguments similar to those applied by Imry and Ma [8] for a random-field Ising model and showed that the susceptibility of the ordered state diverges for d < 4.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…The absence of ferromagnetic ordering in isotropic RAM was first observed in the renormalization group study of [4] where no accessible fixed points of the renormalization group transformation were obtained for the model within ε = 4 − d expansion. Recently, this result was corroborated by higher-order calculations refined by a resummation technique [5]. The proof of [6,7] used arguments similar to those applied by Imry and Ma [8] for a random-field Ising model and showed that the susceptibility of the ordered state diverges for d < 4.…”
Section: Introductionmentioning
confidence: 79%
“…Note once more, that this behaviour is characteristic only of RAM with cubic distribution of random anisotropy axis, described by the effective Hamiltonian (5). A distribution of random anisotropy axis is relevant, i.e., for isotropic distribution, all investigations bring about an absence of a second order phase transition for d 4 [4][5][6][7][8][9][10]12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, there occurs the second order phase transition into the magnetically ordered low-temperature phase. Asymptotically it is characterized by the critical exponents of the random-site Ising model as suggested already in [27] and confirmed later in [28][29][30]. The studies of static criticality of random anisotropy magnets are far from being as intensive as those of the diluted magnets [10], and even less is known about their dynamic critical behaviour.…”
Section: Introductionmentioning
confidence: 75%
“…However, it may occur for an anisotropic distribution. In statics, this situation was corroborated by the RG studies of RAM [26][27][28][29][30] restrictingx to be pointed along one of the 2m directions of the axesk i of a hypercubic lattice (cubic distribution):…”
Section: Introductionmentioning
confidence: 84%